2019
DOI: 10.4995/ijpme.2019.11513
|View full text |Cite
|
Sign up to set email alerts
|

Electrification of Madrid Fleet Public Transport Company (EMT-Madrid): Strategic Analysis and Implementation

Abstract: Madrid Public Transport Company (EMT-Madrid) is a property of the Madrid City Council, and it provides the public buses service in the whole city. Madrid, as most of the big cities in the world, is facing problems related to high levels of urban pollution, which directly affects the health and life quality of their inhabitants. EMT, having a fleet of around 2000 buses, has an impact in the mentioned problem and in the global warming. With the Strategic Plan 2017-2020, many new buses will be acquired, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, there has been no study applying PESTLE analysis in a developing country, particularly a fossil-importing country, that analyzes the adoption of e-PUVs with more inclusive points of view of various public transport stakeholders. Additionally, previous studies applied PESTLE analysis using secondary data [25,29,69,70] and interviews with representatives from car companies [24] as well as vehicle drivers and passengers [26]. This study fills these gaps with three proposed contributions.…”
Section: Literature Gap and Proposed Contributionmentioning
confidence: 97%
See 2 more Smart Citations
“…To the best of our knowledge, there has been no study applying PESTLE analysis in a developing country, particularly a fossil-importing country, that analyzes the adoption of e-PUVs with more inclusive points of view of various public transport stakeholders. Additionally, previous studies applied PESTLE analysis using secondary data [25,29,69,70] and interviews with representatives from car companies [24] as well as vehicle drivers and passengers [26]. This study fills these gaps with three proposed contributions.…”
Section: Literature Gap and Proposed Contributionmentioning
confidence: 97%
“…The study found the environmental advantages of EVs over gasoline cars only if EVs use green electricity, otherwise, EVs will produce greenhouse gases as well. Hernanz et al [25] applied the PESTLE for the external part of the analysis of the electrification of the whole fleet of public transport in Madrid, Spain. The results supported the proposal of switching to a 100% electric fleet as the best option in the long term.…”
Section: Pestle Analysis On Ev Adoptionmentioning
confidence: 99%
See 1 more Smart Citation